Food Consumption Utilization, and Life History Parameters of Helicoverpa armigera (Lepidoptera: Noctuidae) Reared on Diets of Varying Protein Level. Issue 1 (1st February 2019) - Truzi, Caio Cesar; Holzhausen, Hurian Gallinari; Álvaro, José Chamessanga; De Laurentis, Valéria Lucas; Vieira, Natalia Fernanda; Vacari, Alessandra Marieli; De Bortoli, Sergio Antonio
Abstract: Helicoverpa armigera (Hübner) is an important pest of crops worldwide, and several studies have focused on the development of this species on different artificial diets. However, studies evaluating the insect's food consumption and utilization using nutritionally different diets are scarce. The aim of this study was to evaluate the biology and to compare the consumption and use of food by H. armigera larvae on diets with different protein levels provided by several dietary ingredients used in the diets. The nutritional index, the relative consumption rate, the relative metabolic rate, the relative growth rate, and the apparent digestibility were higher in the diet with higher than the optimum level of protein. On the other hand, the conversion efficiency of digested food was lower, resulting in a higher metabolic cost. In terms of biological aspects, larval survival was higher for the diet with optimal protein content and lower for the diet with a higher protein level. The pupal period was longer for the diet with a higher protein content, while pupal survival was lower. Among the evaluated diets, the diet with an optimal protein containing white bean 75 g, wheat germ 60 g, soy bran 30 g, milk powder 30 g, brewer's yeast 37.5 g as the protein sources resulted in a higher net reproductive rate, a shorter time for the population to double in number, and the highest rates of population growth. The results suggest that lower or higher protein contents in the diets of H. armigera negatively affect the biological aspects of this species.